О причинах и механизмах развития закона открытых слогов в праславянском - Чекман, Валерий (Slavistica Vilnensis, 2003)
The article comprises three essays. The first is a discussion of the major hypotheses in the literature concerning possible causes and chronology of the Common Slavic (CSl) law of the open syllable as presented in the well-known works of Bernshtein, Shevelov, Stieber, Carlton, and others.It is demonstrated that the traditional explanations of this phenomenon either are teleological in nature (as if prescribing a general goal for some of the CSl developments), or are based on typologically unverified assumptions (such as generalization of the open syllables to all positions in a word).The second essay considers the structure and primary properties of the so-called dynamic model of the tendency toward open syllables. It is noted, that an obligatory prerequisite to the development of this tendency is an open nature of all word-final syllables. So, the starting point for this tendency in CSl was the loss of all final consonants; the well-known simplifications of consonant clusters were caused by this change. The rise of the nasal vowels, the pleophony/metathesis of TăRT–groups (where R represents both r and l), and, apparently, the development of prothetic consonants are also associated with this tendency. CSl changes that are not associated with the syllabic structure of a word should not be treated as realizations of the open-syllable law.The typological data show also that the tendency toward open syllables in a given language usually is an effect of a strong substratum influence on that language. The last essay of the article discusses which language could produce such an influence on CSl. It is the author’s opinion that the tendency toward open syllables, and other CSl innovations, were the result of influence from Scytho-Sarmatian dialects which could affected CSl dialects in the last centuries B.C. and the first centuries A.D. This proposal takes into account a series of hypotheses about the origin and development of the pre-historic Slavs by the outstanding Russian archaeologist Valentin Sedov.